Meningkatkan Hasil Belajar Peserta Didik Materi Gereja Sebagai Umat Allah Dengan Metode PBL Berbantuan Audio Visual Fase F Kelas XI SMA Negeri 6 Pontianak - Marsius Arianus; Nerita Setiyaningtiyas; Tarsisius Adi Prasetya (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education in Indonesia faces complex challenges, so the government, educational institutions, and society continue to strive to improve access, quality, and relevance of education to form a young generation that is skilled, competitive, and ready to face the challenges of the 21st century. In the context of the Independent Curriculum, Catholic religious education in Indonesia emphasizes the development of religious understanding, moral values, and Catholic spirituality for students, while paying special attention to strengthening the Pancasila Student Profile. This research focuses on the dimension of knowledge and motivation of students to form strong character and mentality for the younger generation in facing various global challenges. Based on the data from the learning evaluation results at SMA Negeri 6 Pontianak, it shows that students' understanding of the Church's material as God's People is still not optimal. One of the reasons is the use of learning methods that are less varied and do not involve students actively in the learning process. Conventional learning models often make students passive and less motivated to dig deeper into the material being studied. So to face this condition, educators need to design a relevant and interesting learning process. One approach that can be applied is Problem Based Learning or problem-based learning. The objectives of this study are to: (1) identify the effectiveness of the Problem Based Learning method in increasing students' understanding of the material of the Church as God's People in grade XI of SMA Negeri 6 Pontianak; (2) seeing an increase in the active participation of students during learning on the material of the Church as God's people in class XI of SMA Negeri 6 Pontianak; (3) measuring the improvement of learning outcomes after the application of the Problem Based Learning method on the material of the Church as God's people in class XI of SMA Negeri 6 Pontianak. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, written tests, and documentation. Data is analyzed through data reduction, presentation in the form of descriptions, graphs, or tables, and drawing conclusions in accordance with the formulation of the problem. The use of the Problem Based Learning model that follows its syntactic steps, such as orientation to the problem, organizing students to learn, guiding individual and group investigations, developing and presenting results, and evaluating the problem-solving process, has proven to be effective in improving students' learning outcomes on the material of the Church as a people of God Phase F class XI SMA Negeri 6 Pontianak.